Early-Life Environmental and Child Factors Associated with the Presence of Disruptive Behaviors in Seven-Year-Old Children with Autistic Traits in the Avon Longitudinal Study of Parents and Children. - Breider, Simone; Hoekstra, Pieter J.; Wardenaar, Klaas J.; van den Hoofdakker, Barbara J.; Dietrich, Andrea; de Bildt, Annelies (Journal of Autism & Developmental Disorders, 2022)
We studied the association of early-life environmental and child factors with disruptive behaviors in children with autistic traits around age 7, in the Avon Longitudinal Study of Parents and Children (n = 6,401). Logistic regression with the least absolute shrinkage and selection operator indicated that disruptive behaviors were associated with prenatal smoking, no seafood-consumption during pregnancy, breech presentation at delivery, neonatal feeding problems, low social-economic situation, suboptimal preschool family environment, maternal depression, maternal antisocial behavior, male sex, and difficult child temperament. Compared to controls, male sex, maternal depression, and suboptimal preschool family environment were related to autistic traits without disruptive behaviors. Thus, there may be a difference in early-life factors related to autism spectrum disorder with and without disruptive behaviors.